Identification and expression analysis of chemosensory receptors in the tarsi of fall armyworm, Spodoptera frugiperda (J. E. Smith) - Dong, Jun-Feng; Yang, Hai-Bo; Li, Ding-Xu; Yu, Hong-Qi; Tian, Cai-Hong (Frontiers in Physiology, 2023)
Chemosensation of tarsi provides moths with the ability to detect chemical signals which are important for food recognition. However, molecular mechanisms underlying the chemosensory roles of tarsi are still unknown. The fall armyworm Spodoptera frugiperda is a serious moth pest that can damage many plants worldwide. In the current study, we conducted transcriptome sequencing with total RNA extracted from S. frugiperda tarsi. Through sequence assembly and gene annotation, 23 odorant receptors (ORs), 10 gustatory receptors (GRs), and 10 inotropic receptors (IRs) were identified. Further phylogenetic relationship analysis with these genes and homologs from other insect species indicated specific genes, including ORco, carbon dioxide receptors, fructose receptor, IRcos, and sugar receptors were expressed in the tarsi of S. frugiperda. Expression profiling with RT-qPCR in different tissues of adult S. frugiperda showed that most annotated SfruORs and SfruIRs were mainly expressed in the antennae, and most SfruGRs were mainly expressed in the proboscises. However, SfruOR30, SfruGR9, SfruIR60a, SfruIR64a, SfruIR75d, and SfruIR76b were also highly enriched in the tarsi of S. frugiperda. Especially SfruGR9, the putative fructose receptor, was predominantly expressed in the tarsi, and with significantly higher levels in the females than in the males. Moreover, SfruIR60a was also found to be expressed with higher levels in the tarsi than in other tissues. This study not only improve our insight into the tarsal chemoreception systems of S. frugiperda but also provide useful information for further functional studies of chemosensory receptors in S. frugiperda tarsi.